Molecular Cooperation between the Werner Syndrome Protein and Replication Protein A in Relation to Replication Fork Blockage - Machwe, Amrita (American Society for Biochemistry and Molecular Biology, 2011)
The premature aging and cancer-prone disease Werner syndrome is caused by loss of function of the RecQ helicase family member Werner syndrome protein (WRN). At the cellular level, loss of WRN results in replication abnormalities and chromosomal aberrations, indicating that WRN plays a role in maintenance of genome stability. Consistent with this notion, WRN possesses annealing, exonuclease, and ATPase-dependent helicase activity on DNA substrates, with particularly high affinity for and activity on replication and recombination structures. After certain DNA-damaging treatments, WRN is recruited to sites of blocked replication and co-localizes with the human single-stranded DNA-binding protein replication protein A (RPA). In this study we examined the physical and functional interaction between WRN and RPA specifically in relation to replication fork blockage. Co-immunoprecipitation experiments demonstrated that damaging treatments that block DNA replication substantially increased association between WRN and RPA in vivo, and a direct interaction between purified WRN and RPA was confirmed. Furthermore, we examined the combined action of RPA (unmodified and hyperphosphorylation mimetic) and WRN on model replication fork and gapped duplex substrates designed to bind RPA. Even with RPA bound stoichiometrically to this gap, WRN efficiently catalyzed regression of the fork substrate. Further analysis showed that RPA could be displaced from both substrates by WRN. RPA displacement by WRN was independent of its ATPase- and helicase-dependent remodeling of the fork. Taken together, our results suggest that, upon replication blockage, WRN and RPA functionally interact and cooperate to help properly resolve replication forks and maintain genome stability.